The Methodology and Implementation of a Knowledge Management System in the Economic Area of a High Polytechnic School: Case Study LABS (2017)
The knowledge management regarding scientific production of the fully employed professors and contributing lecturers of renowned universities is a well-established practice in the major developed countries. Still, substantial improvements in this field are desirable for high polytechnic schools of Southern Europe. This chapter presents a study on knowledge management and analyses trends of a scientific production in the economics and finance area at one of the Portuguese high polytechnic school, namely Lisbon Accounting and Business School (LABS). The data collection methodology regarding scientific research outcomes firstly was proposed and implemented at the economics and finance area. This data collection was based on the direct mail messages addressed to the effective teaching staff members followed by the individual and aggregate analyses of the obtained information regarding published works in the field of economics and finance. The time frame of scientific publications analyses spans over the period of 20 years, namely 1997 - 2016. Later the same methodology was also extended to cover the entire institution. The knowledge management system was implemented in all the knowledge-producing units of LABS. A special database was created to keep the records. It now allows for timely consultation by the administrative bodies of the institution. The main contribution of this study is to demonstrate that the right knowledge management in polytechnic schools is able to unleash hidden potentialities of the capacities evidenced through the implementation of the system of knowledge management. In practical terms, the aggregate results were presented in the form of a report entitled "Creating Knowledge", which was published on the Internet site of the institution. The main findings of this report "Creating Knowledge" were used in the promotion of the LABS towards potential students and represented one of the main factors of fully accomplished enrollment of students for all graduate courses of the LABS for the new academic year beginning in September 2016 at the first stage of the enrollment process.